USING ANALYTIC TEAMS TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING SKILL - Aseptiana Parmawati (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2018)
Speaking is the highest target in English language because speaking is basis of communication which becomes a function learning. There are many kinds of technique to improve speaking skill and one of them is Analytic Teams Technique. Therefore, the researcher wanted to find out whether or not Analytic Teams technique can improve the students’ speaking skill and to analyze the classroom situation when the Analytic Teams technique is implemented in speaking class. This research used Collaborative Classroom Action Research and composed for two or more cycles then it observed and evaluated to identify all facts including the success and the failure of the action. It means that the action should be stopped or continued and revised to the next cycle based on the selected criteria of success. After the implementation of Analytic Teams Technique in every cycle, the students’ speaking score were getting better. It can be seen from the result of students’ average score Cycle 1 was 64.28 and Cycle 2 was 78.05. It can be concluded that Analytic Teams Technique can improve students’ speaking skill and improve speaking classroom into a better situation. Keywords: Analytic Teams; Speaking Skill; CAR